2019
DOI: 10.1016/j.ajog.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical approach on oncologic outcomes in women undergoing radical hysterectomy for cervical cancer

Abstract: BACKGROUND: Recent studies demonstrating shorter survival among cervical cancer patients undergoing minimally invasive versus open radical hysterectomy could not account for surgeon volume and require confirmation in other jurisdictions with larger sample sizes, longer follow-up, and data on disease recurrence. OBJECTIVE: To determine if surgical approach is associated with oncologic outcomes in cervical cancer patients undergoing minimally invasive or open radical hysterectomy, while accounting for mechanist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 40 publications
3
98
1
1
Order By: Relevance
“…Kim et al 15 studied 593 patients with early-stage cervical cancer and found that cervical cancer patients who underwent minimally invasive surgery had significantly worse progression-free survival than those in the open surgery group with tumor size >2 cm and ≤4 cm (p=0.044). In addition, Cusimano et al 14 reported that minimally invasive surgery was associated with a higher rate of recurrence and death compared with the open surgery group in cervical cancer with stage IB1, and that the harm associated with this approach may be independent of surgeon volume.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 15 studied 593 patients with early-stage cervical cancer and found that cervical cancer patients who underwent minimally invasive surgery had significantly worse progression-free survival than those in the open surgery group with tumor size >2 cm and ≤4 cm (p=0.044). In addition, Cusimano et al 14 reported that minimally invasive surgery was associated with a higher rate of recurrence and death compared with the open surgery group in cervical cancer with stage IB1, and that the harm associated with this approach may be independent of surgeon volume.…”
Section: Discussionmentioning
confidence: 99%
“…They include the Laparoscopic Approach to Cervical Cancer (LACC) trial, a randomized controlled phase 3 trial helmed by Pedro Ramirez, MD, director of minimally invasive surgical research and education in the center's Department of Gynecologic Oncology and Reproductive Medicine, and an epidemiologic study led by J. Alejandro Rauh‐Hain, MD, MPH, an assistant professor of gynecologic oncology, reproductive medicine, and health services research. Since the findings were published, several studies in journals such as Gynecologic Oncology , the International Journal of Gynecological Cancer , and the American Journal of Obstetrics and Gynecology have corroborated the results.…”
mentioning
confidence: 64%
“…Cervical cancer is a rare malignancy; surgeons in Ontario have performed a median of 8 radical hysterectomies (interquartile range, 4e12) for cervical cancer annually. 4 This is the reality for most regions in North America and Europe, thanks to screening and vaccination programs. It may take a decade for surgeons to achieve stated targets for proficiency in such settings, and heterogeneity in surgeon volume is inevitable.…”
Section: Replymentioning
confidence: 99%
“…That even some observational studies, which remain susceptible to confounding, have produced comparable results should indeed be cause for concern, in early-stage cervical cancer patients specifically. 4 Open radical hysterectomy must be the recommended approach outside of future randomized trials.…”
Section: Replymentioning
confidence: 99%
See 1 more Smart Citation